Effects of folic acid administration on testicular ischemia/reperfusion injury in rats - Fakouri,Aris (2017)
Abstract Purpose: To determine the effect of folic acid (FA) on experimental testicular ischemia/reperfusion (I/R) in rats. Methods: Sixty male Wistar rats were randomly divided into 6 groups. The control group received physiologic saline orally. The sham-operated group received physiologic saline orally then exposed to midline laparotomy without clamping the IR. The I/R rats received oral gavage of the saline then subjected to 1h ischemia /24h reperfusion, period. In folic acid (2mg/kg+IR) rats received oral gavage of the FA (2mg/kg) then subjected to 1h I/24h R. groups 5-6 received FA (5 and 10 mg/kg), then subjected to 1 h I/24 h, respectively. At the end of the study, semen samples were collected for spermatozoa characteristics. The left testis was removed for histological analysis and superoxide dismutase (SOD), malondialdehyde (MDA) and glutathione peroxidase (GPx) measurement. Results: Spermatozoa mobility, mortality (%) significantly decreased in I/R group (P<0.05). Dose dependent increase observed on spermatozoa mobility, mortality (%) using different levels of the FA (2, 5 and 10 mg/kg) treated rat (P<0.05). Tissue MDA levels significantly increased in I/R rat (P<0.05) while FA (2, 5 and 10mg/kg) in a dose dependent manner decreased I/R-induced MDA (P<0.05). Experimental I/R significantly decreased SOD and GPx activity (P<0.05). Administration of the FA (2, 5 and 10mg/kg) significantly increased tissue SOD and GPx activity in I/R rat (P<0.05). Seminiferous tubules degenerated and loss of spermatogenesis with few spermatocytes was observed in degenerated testis tubules in I/R rat. Orally administration of the FA (5 and 10 mg/kg) improved testis characteristics with few normal seminiferous tubules and spermatocyte in seminiferous tubules in experimental I/R-induced rat. Conclusion: The treatment of folic acid had a benefit effect against ischemia-reperfusion.